ChemInform Abstract: A Straightforward Approach to Tetrahydroindolo[3, 2‐b]carbazoles and 1‐Indolyltetrahydrocarbazoles Through [3 + 3] Cyclodimerization of Indole‐Derived Cyclopropanes. Issue 25 (June 2016) - Ivanova, Olga A.; Budynina, Ekaterina M.; Khrustalev, Victor N.; Skvortsov, Dmitriy A.; Trushkov, Igor V.; Melnikov, Mikhail Ya.
Abstract: Biologically relevant bisindols, e.g. (II) and (IV), are produced via cyclodimerization of indole‐based donor‐acceptor cyclopropanes (I) and (III), respectively.